2020
DOI: 10.1002/jsfa.10792
|View full text |Cite
|
Sign up to set email alerts
|

Submerged fermentation of Ginkgo biloba seed powder using Eurotium cristatum for the development of ginkgo seeds fermented products

Abstract: BACKGROUND Ginkgo biloba seeds are well known for the significant curative effects on relieving cough and asthma. However, the development of products from ginkgo seeds still falls behind at present, resulting in a great waste of ginkgo seeds' resource. In this work, submerged fermentation of ginkgo seed powder using Eurotium cristatum was studied to investigate its feasibility as a new processing method. RESULTS To promote the growth of E. cristatum, the optimum fermentation medium was 80.0 g L−1 of ginkgo se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…On the other hand, Bartkiene et al [9] used SmF to obtain different antioxidant and antimicrobial compounds by fermenting barley by-products with the bacterium Pediococcus acidilactici. In addition, Zou et al [10] also used SmF to enhance antioxidant activity of ginkgo seeds suspension through fermentation with Eurotium cristatum. Finally, agri-food waste cannot only serve as a substrate, but also as a support for fermentation.…”
Section: Fermentation Processesmentioning
confidence: 99%
“…On the other hand, Bartkiene et al [9] used SmF to obtain different antioxidant and antimicrobial compounds by fermenting barley by-products with the bacterium Pediococcus acidilactici. In addition, Zou et al [10] also used SmF to enhance antioxidant activity of ginkgo seeds suspension through fermentation with Eurotium cristatum. Finally, agri-food waste cannot only serve as a substrate, but also as a support for fermentation.…”
Section: Fermentation Processesmentioning
confidence: 99%
“…A lower level of 262.17 ± 17.04 μg/mL was shown at the inoculum amount of 11% (v/v). As it is important to achieve a balance between inoculum size and available nutrients, too high of an inoculum size might result in the nutrient competition of strains on limited substrates ( 37 ). Here, an inoculum size of 2–8% (v/v) was selected for further response surface analysis.…”
Section: Resultsmentioning
confidence: 99%
“…1,5 According to the European Pharmacopeia standard, in standard EGb, the limit of GAs should not exceed 5 ppm. 3,6 The content of GAs in each part of the Ginkgo tree is much higher than this stipulated level. 3 It is reported that the EGb exocarp with higher GAs content had a stronger inhibitory effect on human hepatoma carcinoma (HepG2) cell viability.…”
Section: Introductionmentioning
confidence: 92%
“…Reducing GAs content during manufacturing is one of the critical factors for the exploitation and further research of GBLT products. Various processing methods such as fermentation, 5,6 roasting, 8 and drying 9 have been used to process G. biloba seed, from which the amount of GAs in the seed can be decreased effectively 3 . However, whether such methods effectively reduce GAs content in GBLT products is unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation